Greek Primary School Teachers' Professional Experience as Digital Actors - Giavrimis, Panagiotis (Revija za elementarno izobraževanje, 2023)
The present study investigates teachers’ views on their experience as digital actors in the context of Greek educational policy. The interview was used as a tool for data collection. Findings revealed that the teachers in our survey highlighted the shortcomings of the Greek educational approach in terms of material and technical infrastructure and the training of teachers regarding ICT. Through this new digital context of education, teachers conceptualize their competence and self-efficacy, their self-perception, and their emotional response to integrating new digital tools into teaching practice.